Relationship between acceleration of the foot and lower-leg movement in soccer ball trapping - Tahrar, R.; Shimonagata, S.; Taguchi, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to extract motion characteristics from the changes in foot acceleration, ball velocity after trapping, and lower-limb joint angles with regard to inside trapping of the ball in soccer. Thirteen experienced male collegiate soccer players were asked to perform inside trapping of the ball 10 consecutive times in two different tasks. Acceleration of the foot and bodily movements in trapping were recorded using accelerometers and video cameras. There was a significant correlation between ball velocity after trapping and external rotation of both the hip and knee in the first task (hip, r=-0.62; knee, r=-0.65; p<0.05 for both coefficients). In the second task, there was a significant correlation between the ball velocity after trapping and external rotation of the hip (r=-0.66; p<0.05).